The Effect of Work-Life Balance and Quality of Work Life on Job Satisfaction - Dismas Persada Dewangga Pramudita; Adriana Adela Uri Angesti (LP2M IAIN Palopo, 2025)
This study aims to examine the effect of work-life balance and quality of work life on job satisfaction among employees at Open Your Mind Indonesia. The background of this research is rooted in the growing awareness of the importance of creating a positive work environment that supports employees' well-being and performance. Quality of work life is a multidimensional construct encompassing physical work conditions, managerial support, fair compensation, and opportunities for personal and professional development. Meanwhile, work-life balance reflects the ability of individuals to effectively manage job demands alongside personal life, which is essential to reducing stress and promoting psychological well-being. Quantitative method with data collected through questionnaires distributed to 40 respondents at Open Your Mind Indonesia (OYMI). Data analysis was conducted using SPSS IBM version 29 to test the direct influence between work life balance, quality of work life, and job satisfaction. The results demonstrate that both quality of work life and work-life balance have a significant and positive influence on job satisfaction. Employees who experience better quality of work life and a balanced work-life integration tend to report higher levels of job satisfaction. These findings emphasize the need for organizations to design flexible, supportive, and inclusive work environments to enhance employee satisfaction at work.